ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU SEMEN PADA TALISE PAVING DI KOTA PALU - Baiti, Nurul (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
The purpose of this study is to find out and analyze the optimal number of purchases each time making an order, knowing the safety stock of raw materials that must be provided and knowing when to re-order raw materials. This type of research is quantitative descriptive research, using the EOQ (Economic Order Quantity) method. The results of this study indicate that when using the EOQ method the economical raw material purchase in 2017 is 426.56 zak with the order frequency of 28 times and the optimum cycle time of each order is 10 days. The number of safety supplies that must be provided is 357.81 zak. The right time to re-order is when the raw material supply is 441.31 zak.